Bisphenol A Alters β-hCG and MIF Release by Human Placenta: An In Vitro Study to Understand the Role of Endometrial Cells - C. Mannelli; F. Ietta; C. Carotenuto; R. Romagnoli; A. Z. Szostek; T. Wasniewski; D. J. Skarzynski; Luana Paulesu (Hindawi Limited, 2014)
A proper fetomaternal immune-endocrine cross-talk in pregnancy is fundamental for reproductive success. This might be unbalanced by exposure to environmental chemicals, such as bisphenol A (BPA). As fetoplacental contamination with BPA originates from the maternal compartment, this study investigated the role of the endometrium in BPA effects on the placenta. To this end, in vitro decidualized stromal cells were exposed to BPA 1 nM, and their conditioned medium (diluted 1 : 2) was used on chorionic villous explants from human placenta. Parallel cultures of placental explants were directly exposed to 0.5 nM BPA while, control cultures were exposed to the vehicle (EtOH 0.1%). After 24-48 h, culture medium from BPA-treated and control cultures was assayed for concentration of hormone human Chorionic Gonadotropin (β-hCG) and cytokine Macrophage Migration Inhibitory Factor (MIF). The results showed that direct exposure to BPA stimulated the release of both MIF and β-hCG. These effects were abolished/diminished in placental cultures exposed to endometrial cell-conditioned medium. GM-MS analysis revealed that endometrial cells retain BPA, thus reducing the availability of this chemical for the placenta. The data obtained highlight the importance of in vitro models including the maternal component in reproducing the effects of environmental chemicals on human fetus/placenta.